Investigation of Acid-Etched CO(2) Laser Ablated Enamel Surfaces Using Polarization Sensitive Optical Coherence Tomography - Nahm, Byung J. (2012)
A carbon dioxide laser operating at the highly absorbed wavelength of 9.3μm with a pulse duration of 10–15μs is ideally suited for caries removal and caries prevention. The enamel thermally modified by the laser has enhanced resistance to acid dissolution. This is an obvious advantage for caries prevention; however, it is often necessary to etch the enamel surface to increase adhesion to composite restorative materials and such surfaces may be more resistant to etching. The purpose of the study was to non-destructively measure the susceptibility of laser-ablated enamel surfaces to acid dissolution before and after acid-etching using Polarization Sensitive Optical Coherence Tomography (PS-OCT). PS-OCT was used to acquire images of bovine enamel surfaces after exposure to laser irradiation at ablative fluence, acid-etching, and a surface softened dissolution model. The integrated reflectivity from lesion and the lesion depth were measured using PS-OCT. Samples were also sectioned for examination by Polarized Light Microscopy (PLM). PS-OCT images showed that acid-etching greatly accelerated the formation of subsurface lesions on both laser-irradiated and non-irradiated surfaces (P<0.05). A 37.5% phosphoric acid etch removed the laser modified enamel layer after 5–10 seconds.